An FPGA-based switching photovoltaic-connected inverter topology for leakage current suppression in grid-connected utilizations - Ghaderi, Davood (Wiley, 2020)
This study presents a symmetrical photovoltaic (PV)-connected inverter topology for eliminating the common-state leakage current in grid-connected inverters. A new inverter topology is introduced that minimizes the leakage current, increases efficiency, and is economically viable because it consists of six power switches and two power diodes that, compared with similar ones, consist of the same element numbers. In this inverter, power losses are lower than popular topologies such as H5, H6, and HERIC, and the voltage stresses of the switches are reduced. These features are due to the unique composition of the inverter branches and the location of the switches and diodes and the formation of a suitable freewheeling path for the current. The freewheeling path separates the alternating current (AC) side from the direct current side in the converter and cuts off the PV array leakage current to the AC grid. This will improve network reliability indices and maintain conservation standards. Finally, the content of this method is validated by comparing the proposed inverter with the existing conventional topologies. A prototype has been implemented for the performance analysis of the proposed inverter and results presented.
Keywords: common-state leakage current; grid-connected inverters; photovoltaic; renewable energy sources